Analysis of Work Motivation on CV. Seven Brave - Aa Kartiwa; Indah Permatasari (Journal of Bussines Management Basic, 2022)
CV. Seven Brave is a company engaged in the convection industry, has employees who are not optimal in their work due to several things such as compensation that is not in accordance with the stipulated UMR, the absence of social security provision, etc. Based on this, this study aims to analyze work motivation and efforts to increase work motivation on CV. Seven Braves. This study uses a qualitative research method approach with the research variable is work motivation. The sampling technique was carried out by purposive sampling technique. Research informants amounted to 8 people. The research data were analyzed using the Miles and Huberman model with steps including data collection, data reduction, data presentation, and drawing conclusions. The results of this study that work motivation on CV. Seven Brave as a whole is quite good and has met expectations, with compensation according to company policy, giving bonuses and employee benefits that are adequate, family-friendly employee relations, good training and guidance. Attention is needed in terms of providing compensation in accordance with the stipulated UMR, and social security for workers